Identification of genetic regulatory loci for anthocyanins in wine grape skins - WANG Shanglin; ZHANG Huimin; SUN Qi; PAN Qiuhong; DONG Zhigang; DUAN Changqing; HE Fei (Guoshu xuebao, 2025)
[Objective] Anthocyanins impart the bright colors of pink, red or even purple to grapes and wine, directly influencing their quality and economic value of wine grapes. There are differences in the color characteristics of different structural anthocyanins, and we can understand the genetic predisposition of different structural anthocyanins and mine significantly associated single nucleotide polymorphism (SNP) loci and candidate genes. This series of work will provide solid theoretical support for molecular breeding of grapes with different colors. [Methods] The F1 progeny of the cross between Cabernet Sauvignon 685 (CS 685) and Syrah 100 (X 100) was used as the material, and the phenotypic concentration of each anthocyanin was detected by high performance liquid chromatography-mass spectrometry (HPLC-MS), which provided phenotypic data for the subsequent genome-wide association analysis. In this study, we analyzed the correlation of different anthocyanins. We further analyzed the phenotypic data of anthocyanins and the large amount of SNPs data obtained from whole-genome resequencing, and screened the significant SNP loci and candidate genes associated with the anthocyanins. We explored the intersection of significant SNP loci associated with the different phenotypes. Finally, we analyzed the changes of anthocyanin concentrations caused by the variation of SNP loci, and explored the effects of the different genotypes of SNP loci on the anthocyanin concentration. [Results] A total of 20 anthocyanins were detected in the F1 progeny population of the CS 685 and X 100, and all anthocyanins showed a broad and continuous distribution in the cross progeny population with very high broad-sense heritability. The significant positive correlations were found between almost all the anthocyanins, but the concentrations of Cyanidin-3-O-glucoside (Cy-Glu) and Cyanidin-3-O-caffeolyglucoside (Cy-ca) showed relatively low correlations with the other anthocyanins. The genome-wide association study (GWAS) showed that each phenotype was associated with SNP loci, with a total of 17 382 significant SNPs associated with all phenotypes, the majority of them were located on chromosome 2. By studying the intersection of significant SNP loci in each phenotype, it was found that there were a large amount of intersection in each set, suggesting that there would be a common genetic basis between different floral glycosides regulated by the same loci. The peak patterns of the Manhattan plots of each phenotype were very similar, and all of them had significant SNP clusters on chromosome 2, indicating that the loci related to the synthesis of grape anthocyanin were distributed centrally on the chromosome, but the Manhattan plots of Cy-Glu and Cy-ca showed different characteristics, echoing the results of the correlation analysis. The localization of the genes within±100 kb of significant SNP sites on the grape genome showed that all significant SNP sites corresponded to a total of 7, 127 genes. Based on gene function annotation, three candidate genes related to the anthocyanin biosynthesis with SNP sites located in the coding regions of genes were screened, corresponding to nine SNP sites. They were: MYBA2 (VIT_202s0033g00390): Chr2.14291946; MYBA1 (VIT_202s0033g00410): Chr2.14351887, Chr2.14352034, Chr2.14352082, Chr2.14352093, Chr2.14352108, Chr2.14352751; PIA2 (VIT_202s0087g00100): Chr2.17334610 and Chr2.17347491. The SNP sites screened above were associated with 23 phenotypes except for Cy-Glu and Cy-ca. The SNP sites for Cy-Glu and Cy-ca were not screened out probably due to the low density of them on chromosome 2. The most of the candidate SNP sites and genes associated with the phenotypes were duplicated with each other. The VvMYBA2 and VvMYBA1 were transcription factors involved in the regulation of the biosynthesis of anthocyanins. The homologue of gene VIT_202s0087g00100 in Arabidopsis was annotated as photosensitive phytochrome-interacting ankyrin-repeat protein 2 (PIA2), which was a positive regulator of anthocyanin accumulation in Arabidopsis. The analysis examined the effect of SNP locus genotypes on the concentration of acylated anthocyanins, unacylated anthocyanins, F3’H anthocyanins, F3’5’H anthocyanins and total anthocyanins. The Chr2.14291946 had two genotypes, that was, GG and GC, corresponding to a significantly higher phenotypic concentration of GC than GG. The Chr2.14351887 had three genotypes, that was, AA, AG and GG, corresponding to a significantly higher phenotypic concentration of GG than AG, and AG than AA. The Chr2.14352034 had three genotypes, that was, TT, TG and GG, corresponding to the phenotypic concentrations. GG was significantly higher than TG, TG was significantly higher than TT, but for F3’H anthocyanin, GG was not significantly different from TG. The Chr2.14352093 had three genotypes, that was, AA, AC and CC, corresponding to phenotypic concentrations. CC was significantly higher than AC, AC was significantly higher than AA, but for F3’H anthocyanin, CC was not significantly different from AC. The Chr2.14352108 had three genotypes, that was, CC, CA and AA, which corresponded to a significantly higher phenotypic concentration of AA than CA, CA than CC, but for F3’H anthocyanin, there was no significant difference between AA and CA. Chr2.14352751 had two genotypes CC and CT, and CT corresponded to a significantly higher phenotype concentration than CC. Chr2.17334610 had two genotypes GG and GT, and GT corresponded to significantly higher phenotype concentration than GG. Chr2.17347491 had three genotypes TT, TC and CC, corresponding to the phenotype concentration of CC was significantly higher than TC, TC was significantly higher than TT, but for F3’H anthocyanin, CC was not significantly different from TC. Chr2.14352093, Chr2.17347491 were synonymously mutated, but could still have an effect on the phenotype because synonymous mutations could affect transcriptional level regulation, translation efficiency, and other dimensions. The Chr2.14291946, Chr2.14351887, Chr2.14352034, Chr2.14352082, Chr2.14352108, Chr2.14352751, and Chr2.17334610 had non-synonymous mutations encoding altered amino acids. [Conclusion] All of these SNP loci seems to be possible to develope as molecular markers. The results of the study would provide targets for the study of the regulatory mechanism of grape anthocyanin synthesis and theoretical support for molecular breeding of grapes with different fruit colors.